Role of Non-Vitamin K Oral Anticoagulants for Prevention of Stroke in Renal Impaired Atrial Fibrillation Patients - Budi Yuli Setianto (ACI (Acta Cardiologia Indonesiana), 2019)
Atrial fibrillation (AF) and chronic kidney disease (CKD) are highly prevalent, particularly with increasing of age and associated comorbidities, such as hypertension, diabetes, heart failure, and vascular disease. The relationship between AF and CKD seems to be bidirectional. CKD predisposes to AF while onset of AF seems to lead to progression of CKD. Stroke prevention is the cornerstone of AF management, and AF patients with CKD are at higher risk of stroke, mortality, cardiac events, and bleeding. Stroke prevention requires use of oral anticoagulants, which are either vitamin K antagonists (e.g. warfarin), or the non-vitamin K antagonist oral anticoagulants (NOAC). While NOAC have been shown to be effective in mild-to-moderate renal dysfunction, there are a paucity of data regarding NOAC in severe and end-stage renal dysfunction. The followingwill discuss the evidence for NOAC in CKD, and summarize the current knowledge regarding the efficacy and safety of NOAC to prevent AF-related stroke and systemic embolism in severe and end-stage renal disease.